O₂·- and NO-associated mechanisms of selective action of redox-active cobalt complexes on tumor tissue - Ganusevich, I.I.; Burlaka, A.P.; Sidorik, E.P.; Levitin, I.Ya; Sigan, A.L.; Osinsky, S.P. (Experimental Oncology, 2007)
Aim: To study the influence of redox-active cobalt(III) complex with tetradentate Schiff base and nicotinamide as an axial ligand on the rate of superoxide radical-anions generation and levels of NO in tumor and normal tissues of Lewis lung carcinoma bearing mice as well as activity of matrix metalloproteinases 2 and 9 (MMPs) in tumor. Methods: The superoxide radical-anions formation and NO level in tissues were assessed by EPR method with the use of 1-hydroxy-2,2,6,6-tetramethyl-4-oxopiperidin and diethyldithiocarbomate spin traps, respectively. MMPs activities were determined by zymography in polyacrylamide gel. Results: It was observed that the rate of superoxide radical-anions generation was selectively increased in tumor tissue (by a factor of 6–7) accompanied with the decrease of NO level (by a factor of 2) due to tested complex administration. Activities of MMPs in tumor were significantly decreased. Conclusion: It is supposed that the one of mechanisms of detected earlier antimetastatic effect of complex is based on its ability to induce the formation of high level of superoxide radical-anions selectively in the tumor tissue that results in the damage of its regulatory functions, in particular alteration in the regulation of NO-synthase, decrease of NO generation as well as activities of MMPs. Цель: исследовать влияние редокс-активного комплекса кобальта (III) с тетрадентатным основанием Шиффа и никотинамидом
в качестве аксиального лиганда на уровень образования супероксидного радикал-аниона и оксида азота в опухолевой и
нормальных тканях мышей с карциномой Льюис и установить взаимосвязь этих показателей с активностью ММП-2 и -9 в
опухоли. Методы: электронный парамагнитный резонанс при комнатной температуре и температуре жидкого азота (77 °К),
технология Spin Traps, зимография в полиакриламидном геле. Результаты: установлено, что под действием комплекса в
опухолевой ткани мышей с карциномой Льюис селективно повышается (в 6–7 раз) скорость образования супероксидных
радикал-анионов и снижается (в 2 раза) уровень образования радикальных форм оксида азота; при этом значительно
снижается активность ММП-2 и -9. Выводы: высказывается предположение, что в основе механизма установленного ранее
антиметастатического действия изученного комплекса кобальта лежит его способность селективно создавать сверхвысокие
уровни супероксидного радикал-аниона в опухолевой ткани, что приводит к нарушению его регуляторных функций, в частности
к изменению регуляции NO-синтаз, снижению продукции NO и активности желатиназ.